2013
DOI: 10.1007/s00198-012-2264-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospital burden of vertebral fractures in France: influence of vertebroplasty

Abstract: This is the first French study assessing the national burden of vertebral fractures based on hospital data. In-hospital death rate is lower in patients with vertebroplasty, who are younger and have less comorbidities than the general population with vertebral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“… 497 ≥65 Plain lateral radiographs of thoracic and lumbar spine with collapse of the anterior and posterior borders at >15% of its normal height Levy et al [ 19 ] America Evaluate outcomes in vertebral fragility fracture patients treated operatively and non-operatively over 10 years. 250 Not stated ICD-9 (cod 805.2, 805.4) Maravic et al [ 20 ] France Study of hospital burden and outcomes of patients treated with vertebroplasty or non-operatively admitted into French hospitals with vertebral fragility fractures identified from the 2009 French Hospital National Database. Data collected from admission till 1 year after hospitalisation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 497 ≥65 Plain lateral radiographs of thoracic and lumbar spine with collapse of the anterior and posterior borders at >15% of its normal height Levy et al [ 19 ] America Evaluate outcomes in vertebral fragility fracture patients treated operatively and non-operatively over 10 years. 250 Not stated ICD-9 (cod 805.2, 805.4) Maravic et al [ 20 ] France Study of hospital burden and outcomes of patients treated with vertebroplasty or non-operatively admitted into French hospitals with vertebral fragility fractures identified from the 2009 French Hospital National Database. Data collected from admission till 1 year after hospitalisation.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported the incidence of hospital admission with vertebral fragility fracture using large national hospital databases of Spain [ 8 ], America [ 9 ], Hungary [ 12 ], Italy [ 13 ], Sweden [ 17 ] and France [ 20 ]; and Medicare, an American national insurance programme dataset [ 10 ]. There was geographical variation in the overall incidence of hospital admission from 2.8 to 19.3 per 10,000/year (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the attending physicians were masked as to the procedure, so that discharge decisions were based on clinical improvement rather than treatment allocation. Shorter inpatient hospital stays and lower readmission rates for patients treated with VA have been described previously 36 37…”
Section: Prospective Randomized Blinded Outcome Controlled Trialsmentioning
confidence: 76%
“…An analysis of 13,624 hospitalized patients with VCFs from the French Hospital National Database demonstrated that a higher proportion of patients are discharged in 7 days after vertebroplasty compared with medical management (68% versus 47%, P Ͻ .001). 60 A large Taiwanese study using National Health Insurance data for 9238 hospitalized patients with VCFs demonstrated a 2-day-earlier discharge and lower 30-day readmission rates after vertebroplasty.…”
Section: Hospital Admissionmentioning
confidence: 98%